Thermal and rheological measurement techniques for nanomaterials characterization - Thomas, Sabu; Thomas, Raju; Zachariah, Ajesh K. 1983-; Mishra, Raghvendra Kumar (Micro and Nano Technologies, 2017)
Thermal and Rheological Measurement Techniques for Nanomaterials Characterization, Second Edition covers thermal and rheological measurement techniques, including their principle working methods, sample preparation and interpretation of results. This important reference is an ideal source for materials scientists and industrial engineers who are working with nanomaterials and need to know how to determine their properties and behaviors.--Provided by publisher.